Whirlpool in the Caribbean Community : the services sector in 1993 and beyond. - ZAGARIS, Bruce (1993)
Looks at current extraregional policies that impact on Caribbean states. Focuses on areas in which Caribbean countries - and using Barbados as the example - can develop, viz. financial services, taxation, tourism.